PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP PEMAHAMAN AKUNTANSI (Studi Empiris Mahasiswa Jurusan Akuntansi Perguruan Tinggi Berbasis Islam di Malang) - Moh. Abdul Azis; Maslichah Maslichah; Afifudin Afifudin (Universitas Islam Malang, 2018)
ABSTRAKThis study aims to examine the intellectual, emotional intelligence,spiritual intelligence partial effect to the understanding of accounting.Thistype of research is a correlation study using a quantitative approach.Correlation research is research conducted to determine the level ofrelationship between two variables or more without making any changes,additions or manipulation of existing data variables are obtained based on dataand facts are derived from the questionnaire that will be distributed. Thisstudy is intended to determine how the contribution of independent variablessuch as intellectual, emotional intelligence and spiritual intelligence on thedependent variable understanding of accounting, as well as the direction of therelationship occurred. Respondents in this study were students of batch 2014accounting of several campuses Mebel namely University of Islamic Malang,University of Muhammadiyah Malang, Islamic State University MaulanaMalik Ibrahim Malang.Keywords: to intellectual Intelligence, Emotional Intelligence, SpiritualIntelligence. understanding of Accounting